Analysis of Factors and Situations Influencing Preventive Behaviours for the Spread of COVID-19 in Adults with Chronic Diseases and Older Adults - Achmad Syukkur; Berliany Venny Sipollo (Babali Health, 2022)
Introduction: The older adults and people with comorbidities are more susceptible to the infected of the COVID-19 virus, and have a higher risk of mortality compared to other populations. Steps to prevent transmission have been taken by the government, such as socializing physical distancing movements, staying at home, wearing masks when leaving the house, to prohibiting people from going to village. This study wants to know the factors and situations that influence the behaviour of preventing COVID-19. Methods: This research design uses observational design with correlation description approach. The total population is 148, obtained a sample of 126 respondents using the Slovin’s formula. Random sampling technique used with the help of the excel application. The older adult’s group was 63 respondents and the chronic disease group was 63 respondents. The researcher used 11 questionnaires and multivariate analysis test results using SEM with SmartPLS. Results: The results of the multivariate analysis test using SEM (Structural Equation Modeling) with SmartPLS (Partial Least Square) showed that the factors that influenced COVID-19 prevention behaviour in the older adult’s group were knowledge, while in the chronic disease group was social support and attitude towards COVID-19. Conclusion: It is hoped that it can improve preventive behaviour against COVID-19 by understanding what factors are weakening or factors that can increase the risk of COVID-19 transmission in the elderly and people with chronic diseases, and can be a policy reference in implementing the protocol of COVID-19 for the Village Government.